The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.7759/cureus.23656
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutations in Colorectal Cancer: Relationship With Clinicopathological Characteristics and Impact on Clinical Outcomes in Saudi Arabia

Abstract: Background Few studies have addressed the prevalence and prognostic impacts of KRAS mutations in Saudi patients with colorectal cancer (CRC). The present study aimed to address the prevalence of KRAS mutations and evaluate their impact on clinical outcomes (if any) among Saudi patients. Methods This retrospective cohort study was conducted at King Saud University Medical Centre (KSUMC), Saudi Arabia. All medical records of biopsy-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…The frequency of KRAS mutations (exon 2 and exon 3) in our cohort reached 61.88%. This was much higher than what was reported in the Asia-Pacific (37-52%) and Western populations (32-49%) [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Nevertheless, our data is in line with a previous study in Indonesia, showing that KRAS mutation was found in 71.8% of serrated adenocarcinoma (SA), which is intriguingly higher than the generally reported incidence of 40% [39][40][41].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The frequency of KRAS mutations (exon 2 and exon 3) in our cohort reached 61.88%. This was much higher than what was reported in the Asia-Pacific (37-52%) and Western populations (32-49%) [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Nevertheless, our data is in line with a previous study in Indonesia, showing that KRAS mutation was found in 71.8% of serrated adenocarcinoma (SA), which is intriguingly higher than the generally reported incidence of 40% [39][40][41].…”
Section: Discussionsupporting
confidence: 82%
“…Consequently, our high co-mutation rate in the Indonesian population can shed new light that warrants further investigation. This study and others have shown that KRAS mutation was more frequent in right sided CRC [37,54,55]. The predilection of KRAS mutations for the right side of the colon may be influenced by the fact that the right and left side of the colon have different biology and histopathology in their respective embryological origins [37,56,57].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Interestingly, among these genes, the highest number of genetic interactions were found for KRAS (Fig. 3E), which had important roles in the occurrence and development of diverse cancers [37,38]. These findings confirmed a crucial role and great potential application of KRAS in synthetic lethality.…”
Section: Expression Profiles Of Involved Genessupporting
confidence: 61%
“…However, other studies have reported conflicting results with our study and have found no significant difference in survival outcomes between mutant and wild type in mCRC. For example, a study published in 2022 by Alghamdi et al found that KRAS mutational status did not significantly affect OS or progressionfree survival in patients with mCRC [15]. This inconsistency in the literature may be due to differences in study design, patient populations, and treatment regimens.…”
Section: Limitationsmentioning
confidence: 99%